PENDAMPINGAN PARTISIPATIF BERBASIS SOSIAL-EKONOMI DALAM OPTIMALISASI BUDIDAYA SEMANGKA TANPA BIJI DI SLEMAN - Kastono, Dody; Untari, Dyah Woro; Azzahrah, Unaitsa; Subejo, Subejo; Utami, Sri Nuryani Hidayah; Harjaka, Tri; Ansari, Andrianto; Muttaqin, Andi Syahid; Akhda, Najmu Tsaqib; Widada, Arif Wahyu; Danindra, Septian Adira (Kumawula: Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service program aims to address low productivity and improve the implementation of Standard Operating Procedures (SOPs) for seedless watermelon cultivation in Sleman Regency, Special Region of Yogyakarta, from November 2023 to January 2025. Farmers face obstacles in land management, fertilization, and pest control, and are influenced by limited capital, fertilizer availability, and traditional farming mindsets. This activity aims to improve farmers' ability to partner with the private sector to achieve the target of supplying five tons of watermelon per week. The implementation method uses a participatory empowerment model that actively involves farmers in the processes of problem identification, training, application of cultivation technology, and evaluation of activities. The implementation of activities includes problem identification, technical cultivation training according to SOPs, direct field assistance, and evaluation of results using the before-and-after method to compare changes in SOP implementation and productivity achievements before and after mentoring. Evaluation indicators include the level of SOP implementation, harvest productivity (tons/ha), and yield quality based on watermelon grading. The results of the activity showed an increase in SOP implementation, especially in bed preparation, balanced fertilization, and integrated pest control. Farmer productivity in several planting cycles reached more than 10 tons/ha, with the highest achievement of 18.78 tons/ha, while the average productivity was close to the target range of 5–10 tons/ha. In terms of yield quality, the percentage of Grade A fruit among some farmers reached 31.64–36.08%, close to the quality target of 30–50%, while Grade B fruit still dominated the yield, ranging from 44.87–63.92%. From a socio-economic perspective, this activity also strengthened farmers' ability to manage their businesses and expand market access through the integration of sustainable partnerships.Program pengabdian kepada masyarakat ini dilakukan untuk mengatasi rendahnya produktivitas dan belum optimalnya penerapan Standar Operasional Prosedur (SOP) budidaya semangka tanpa biji di Kabupaten Sleman, Daerah Istimewa Yogyakarta selama November 2023 hingga Januari 2025. Petani menghadapi kendala dalam pengelolaan lahan, pemupukan, dan pengendalian hama, serta dipengaruhi oleh keterbatasan modal, ketersediaan pupuk, dan pola pikir tradisional dalam bertani. Kegiatan ini bertujuan untuk meningkatkan kemampuan petani untuk bermitra dengan sektor swasta agar mampu mencapai target pasokan lima ton semangka per minggu. Metode pelaksanaan menggunakan pendekatan participatory empowerment model yang melibatkan petani secara aktif dalam proses identifikasi masalah, pelatihan, penerapan teknologi budidaya, dan evaluasi kegiatan. Pelaksanaan kegiatan meliputi identifikasi masalah, pelatihan teknis budidaya sesuai SOP, pendampingan langsung di lapangan, serta evaluasi hasil menggunakan metode before-after untuk membandingkan perubahan penerapan SOP dan capaian produktivitas sebelum dan sesudah pendampingan. Indikator evaluasi meliputi tingkat penerapan SOP, produktivitas panen (ton/ha), dan kualitas hasil berdasarkan grading buah semangka. Hasil kegiatan menunjukkan adanya peningkatan penerapan SOP, terutama dalam pembuatan bedengan, pemupukan berimbang, dan pengendalian hama terpadu. Produktivitas petani pada beberapa siklus tanam mencapai lebih dari 10 ton/ha, dengan capaian tertinggi sebesar 18,78 ton/ha dan rata-rata produktivitas kategori mendekati target berada pada kisaran 5–10 ton/ha. Dari aspek kualitas hasil, persentase buah Grade A pada beberapa petani mencapai 31,64–36,08%, mendekati target mutu 30–50%, sedangkan komposisi Grade B masih mendominasi hasil panen dengan kisaran 44,87–63,92%. Dari sisi sosial-ekonomi, kegiatan ini juga memperkuat kemampuan petani dalam manajemen usaha dan memperluas akses pasar melalui integrasi kemitraan yang berkelanjutan.